The Image and the Subject in Russian Monumental Sculpture of the Second Half of the 19th Century. On the Problem of Relations between a Sculptor and a Spectator - Kalugina, Olga V. (Actual Problems of Theory and History of Art, 2018)
In the second half of the 19th century European monumental plastic experienced great creative enthusiasm. In Russia, this process fully manifested itself as well. The nature of imaginative solutions and ways to implement them undergoes marked changes compared with the first half of the century. First of all, this is due to the changing role of the viewer. The viewer becomes a much more active participant in the process of creative problem formulation, selection of the project, its adjustment and evaluation of the result. Expansion of the social base of the recipient of the monumental image sets new demands to the master. Naturally, he begins to focus on less prepared audience. Such an approach brings about many changes in the choice of means of expression, including active introduction of additional information accents. As a result, in a number of projects their subject becomes a much more active participant in composition than the actual plastic image, traditionally oriented to the presentation of a human body. This has a direct impact on a number of creative principles. For example, master’s attitude to the material changes fundamentally correcting issues of proportioning and zooming in sculpture. One striking example of this new method of construction of the sculptural image is “The Monument to was the 1000th anniversary of Russia” in Novgorod. Representatives of the Moscow school of sculpture of the 19th— 20th centuries were to overcome this lack of independent creative thinking.